Organic and conventional tomato cropping systems (Scientia Agricola, 2004)
Among several alternative agricultural systems have been developed, organic agriculture has deserved increasing interest from. The objective of this paper was comparing both organic (OS) and conventional (CS) tomato cropping systems for varieties Débora and Santa Clara, through an interdisciplinary study. The experiment was set up in a randomized blocks design with six replicates, in a dystrophic Ultisol plots measuring 25 ´ 17 m. Cropping procedures followed by either local conventional or organic growers practices recommendations. Fertilization in the OS was done with organic compost, single superphosphate, dolomitic limes (5L, 60 g, and 60 g per pit), and sprayed twice a week with biofertilizer. Fertilization in the CS was done with 200 g 4-14-8 (NPK) per pit and, after planting, 30 g N, 33 g K and 10.5 g P per pit; from 52 days after planting forth, plants were sprayed once a week with foliar fertilizer. In the CS, a blend of insecticides, fungicides and miticides was sprayed twice a week, after planting. In the OS, extracts of black pepper, garlic, and Eucalyptus; Bordeaux mixture, and biofertilizer, were applied twice a week to control diseases and pests. Tomato spotted wilt was the most important disease in the OS, resulting in smaller plant development, number of flower clusters and yield. In the CS, the disease was kept under control, and the population of thrips, the virus vector, occurred at lower levels than in the OS. Variety Santa Clara presented greater incidence of the viral disease, and for this reason had a poorer performance than 'Débora', especially in the OS. Occurrence of Liriomyza spp. was significantly smaller in the OS, possibly because of the greater frequency of Chrysoperla. The CS had smaller incidence of leaf spots caused by Septoria lycopersici and Xanthomonas vesicatoria. However, early blight and fruit rot caused by Alternaria solani occurred in larger numbers. No differences were observed with regard to the communities of fungi and bacteria in the phylloplane, and to the occurrence of weeds.